PULMONARY REHABILITATION PULMONAR IN CHILDREN WITH ASTHMA: BIBLIOGRAPHIC REVISION (Fiep Bulletin - online, 2015)
INTRODUCTION: The diseases of respiratory system are each day more common in children and adolescents lives, especially asthma.  OBJECTIVE: Identify pulmonary rehabilitation plans benefits in asthma patients.  METHOD: This research is about a bibliographic review that was done through a scientific articles selection from Scientific Electronic Library (SCIELO) data base, Scientific Literature of Latin America and the Caribbean (LILACS) and Scholar Google, with the research occurring from March to April of 2014, using the descriptors extracted from HSD (Health Science Descriptors): asthma, physiotherapy and children, using papers from 2004 to 2014. RESULTS: From 616 articles found out just six were included in the revision. The studies showed that the physiotherapy becomes satisfactory in the matter of asthma crisis prevention. CONCLUSION: The management of asthma prevention and treatment isn't completely defined, therefore is evident that the pulmonary rehabilitation turns possible asthma patients better life quality.
Keywords: Asthma. Children. Physiotherapy.